Association between hypoglycemia and poor clinical outcomes in hospitalized non-diabetic patients with liver cirrhosis:– a narrative review - Govindarajan, Rohit; Chen, Jiancong; Zhang, Kunsong; Hu, Wenjie; Xu, Dan; Kuang, Ming (Frontiers in Medicine, 2025)
Hypoglycemia is rarely highlighted as a complication that requires close monitoring in patients with chronic liver disease, despite substantial evidence of its occurrence in cirrhotic patients. This narrative review aims to evaluate whether hypoglycemia in liver cirrhosis patients, irrespective of diabetes status, exacerbates complications and warrants targeted management strategies. Our analysis reveals that hypoglycemia is prevalent in cirrhotic patients and is associated with increased mortality and complications compared to normoglycemic patients. Although literature in this topic is limited, our review suggests that early identification of high-risk liver disease patients and the implementation of novel, clinically relevant strategies to minimize hypoglycemia may improve clinical outcomes and health-related quality of life as well as reduce morbidity and mortality. Further research will be required to validate thesel strategies.